دور مناهج التربية الإسلامية المقررة لطلبة المرحلة الأساسية العليا في مواجهة التطرف الفكري من وجهة نظر معلمي التربية الإسلامية في قصبة الطفيلة - أبو لطيفة، شادي فخرى (الجامعة الإسلامية بغزة - شئون البحث العلمي والدراسات العليا, 2020)
هدفت الدراسة إلى: معرفة دور مناهج التربية الإسلامية المقررة لطلبة المرحلة الأساسية العليا في مواجهة التطرف الفكري من وجهة نظر معلمي التربية الإسلامية في قصبة الطفيلة. واعتمد الباحث المنهج الوصفي الذي يقوم على دراسة الظاهرة كما توجد في الواقع؛ ليصفها وصفاً دقيقاً. تكونت عينة الدراسة من جميع معلمي ومعلمات التربية الإسلامية، الذين يدرسون المرحلة الأساسية العليا في مديرية التربية والتعليم في قصبة الطفيلة، والبالغ عددهم (122) معلماً ومعلمة، ولتحقيق هدف الدراسة؛ قام الباحث بتطوير استبانة مكونة من (30) فقرة، مشتملة على محورين رئيسين: المحور الأول: البيانات الأساسية لأفراد الدراسة. والمحور الثاني: الفقرات المتعلقة بدور مناهج التربية الإسلامية المقررة لطلبة المرحلة الأساسية العليا في مواجهة التطرف الفكري من وجهة نظر معلمي التربية الإسلامية في قصبة الطفيلة. ومن أهم النتائج التي توصلت إليها الدراسة: أن المتوسط الحسابي حسب استجابة عينة الدراسة لمستوى دور مناهج التربية الإسلامية المقررة لطلبة المرحلة الأساسية العليا في مواجهة التطرف الفكري من وجهة نظر معلمي التربية الإسلامية في قصبة الطفيلة جاء على المستوى الكلي بدرجة متوسطة، بمتوسط حسابي (3.46). The target of the study To identify the role of Islamic Education Curriculums for Higher Elementary Students in facing Intellectual Extremism From the point of view of Islamic Education teachers in the schools of Qasabat Al-Tafelah District. The researcher has adopted the Descriptive approach which depends on studying the phenomenon as it is in reality, giving a precise description of it. The study sample consists of all Islamic Education Teachers, teaching the Higher Elementary Students in the Directorate of Education of Qasabat Al-Tafelah District, reaching in number (122) teachers from both genders. To achieve the target of the study, the researcher has developed a questionnaire consisting of (30) articles, covering two major domains, the First Domain is: The Basic Data of individuals participating in the study. The Second domain is: The articles related to the role of Islamic Education curriculums for higher elementary students in facing Intellectual Extremism From the point of view of Islamic Education teachers in Qasabat Al-Tafelah District. Among the major conclusions of the study, is that the average response of the sample study on the effect of the role of Islamic Education Curriculums - for Higher Elementary Students in facing Intellectual Extremism from the point of view of Islamic Education teachers in Qasabat Al-Tafelah District - was mediocre, as the arithmetic average was (3.46).
Keywords: التطرف الفكري -- المناهج الدراسية -- التربية الإسلامية -- أعضاء هيئة التدريس